2012
DOI: 10.15580/gjer.2012.4.102512153
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of the Assessment Structure of the O’level History Syllabus [2167] in Zimbabwe: A Case Study of Zaka District.

Abstract: This study examined teachers' perceptions of the assessment structure on the 0'level History Syllabus 2167 examination in Zimbabwe. A descriptive survey approach in which 30 History teachers from 15 Zaka District secondary schools responded to a questionnaire was used. Quantitative and qualitative paradigms of data presentation were both useful in this project. Findings from the study revealed that assessment and teaching History are two sides of the same coin but dropping the Source Based Question to an optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…That may have been the case because the examination's design absolves history teachers who admit to being ignorant of how to teach for the source-based question, which permits the non-teaching of the question. The results corroborate several studies (Fogo, 2014;Kellaghan & Greaney, 2020;Mapetere et al, 2012;Van Hoover & Yeager, 2013) that assert that even in cases where pre-service teachers were instructed in source-based teaching methodologies, they were often neglected because of the emphasis placed on the textbook and examinations.…”
Section: Examination Oriented Teachingsupporting
confidence: 87%
See 2 more Smart Citations
“…That may have been the case because the examination's design absolves history teachers who admit to being ignorant of how to teach for the source-based question, which permits the non-teaching of the question. The results corroborate several studies (Fogo, 2014;Kellaghan & Greaney, 2020;Mapetere et al, 2012;Van Hoover & Yeager, 2013) that assert that even in cases where pre-service teachers were instructed in source-based teaching methodologies, they were often neglected because of the emphasis placed on the textbook and examinations.…”
Section: Examination Oriented Teachingsupporting
confidence: 87%
“…The teaching of critical thinking skills is not an easy process. For example, in Zimbabwe and South Africa, lack of orientation, poor teacher preparation, learning support materials that are frequently out of print or insufficiently used in the classroom, large class sizes, and the continued use of traditional exams for assessment all hinder the teaching of critical thinking skills (Dube & Moyo, 2022;Dombo & Mujere, 2023;Godsell, 2022;Mapetere et al, 2012). That being so, however, there is no one answer that provides the strategies that can be used to teach critical thinking skills in history teaching.…”
Section: Critical Thinking Skills and History Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the revelation that a History candidate could pass the examination without responding to the higher order question impacted negatively on the History 2167 syllabus. A study by Mapetere, Makaye & Muguti, (2012) in Zaka district in Zimbabwe concluded that the tri-segmented structure of essay questions gave prominence to factual regurgitation and prevented History students from developing genuine higher order skills.…”
Section: In the Opinion Of Mr Chitondomentioning
confidence: 99%
“…In most cases assessment has remained content based thus undoing the skills approach suggested by 'new 'History. Mapetere, Makaye and Muguti (2012) observe that in the current 'O 'level History syllabus 2167, pupils may pass the final examination with at least a B grade without attempting part C of the question which applies skills enshrined in the new History concept.…”
mentioning
confidence: 99%